(untitled) (Research, Society and Development, 2022)
Pregnancy is a period of physical and functional transformations for the maternal organism, as well as anabolic reactions of fetal development. During pregnancy there is a rapid cell division that will start the formation of tissues in the embryo, so folic acid supplementation is very effective in this process. Objective: To analyze bibliographic evidence on the benefits of folic acid supplementation for the mother-baby binomial. Methodology: This is an integrative review study of a qualitative nature, exploratory with a theoretical approach, with a time frame from 2016 to 2022, carried out in the Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED) and Google Scholar databases, using the following descriptors: “Folic acid”, “Vitamin deficiency”, “Nutritional Supplements”, “Pregnant”, “Child”; in Portuguese and English. Conclusion: Folic acid supplementation can guarantee many benefits for maternal and child health: reduction of neural tube deformations (myelomeningocele), protection against non-syndromic cleft lip, decrease in the risk of heart disease and genetic defects, improvement in cognitive and motor, higher levels of concentration and reduction of syndromes such as autism spectrum disorder in babies. For maternal health, lower risk of preeclampsia, reduction of gestational hypertension and preterm birth. Therefore, it is recommended that folic acid supplementation be done in a personalized way, according to the situation of each pregnant woman, in order to respond to the needs of each one during this period.